The Effect of Service Quality on Passenger Loyalty with Passenger Satisfaction as a Moderating Variable (Case Study on Garuda Indonesia Airline Passengers) - Kunto Wibisono; Budi Setyanta; Siti Kusandhitasari Jayaningrum; Muhammad Rifai Arief; Natalia Yesika Tumanggor (Cita Konsultindo Research Center, 2023)
This research is a quantitative and causal associative research with a number of respondents as many as 200 people, a case study was carried out on passengers of Garuda Indonesia Airlines who flew to or from the Special Region of Yogyakarta with the provision that they had used the services of Garuda Indonesia Airlines 2 times. The questionnaire used was in the form of google form. The hypothesis in this research is that the quality of service affects the loyalty of Garuda Indonesia airline passengers is accepted and the quality of service affects passenger loyalty with passenger satisfaction as a moderating variable is not accepted with the assumption of passenger satisfaction as a predictor or independent variable.